FARMERS' PERCEPTIONS OF THE ROLE OF GAPOKTAN IN THE IMPLEMENTATION OF SERASI PROGRAM IN TANJUNG LAGO DISTRICT, BANYUASIN REGENCY - Siska Tri Wulandari; Elisa Wildayana; Desi Aryani (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Farmers' perception of the role of Gapoktan is one of the factors driving farmer participation in agricultural activities and Gapoktan institutions in Tanjung Lago District, Banyuasin Regency. This study aims to (1) analyze farmers' perceptions of the combined role of farmer groups in the implementation of the Save Rawa Prosperous Farmers (Serasi) program in Tanjung Lago District, Banyuasin Regency; (2) analyze the differences in the income of rice farmers before and after the Serasi program in Tanjung Lago District, Banyuasin Regency. The method used in this study is a survey; the data types used are primary data and secondary data. The selection of research locations was carried out purposively, considering that the Tanjung Lago sub-district is one of the sub-districts with a large swamp area. In the application of the Serasi program, there is an active Gapoktan, and the majority of the farmers cultivate rice. The results shown in this study are (1) Farmers' perceptions of the role of Gapoktan in implementing the Serasi program in Tanjung Lago District, Banyuasin Regency in the category of farmer's role as a processing unit of 257.4 (High), the category of Gapoktan's role as a processing unit of 267.2 (Very High), the category of Gapoktan's role as facilities and infrastructure is 268.4 (Very High) and the category of Gapoktan's role as marketing unit is 271.6 (Very High); (2) there is an increase in the income of rice farmers before the Serasi program with an average income of Rp. 53,512,267/year and Rp. 71,505,884/year. Suggestionsgovernment should follow up on the sustainability of the Serasi program because it is very effective in increasing rice production and the economy. Efforts are needed to increase farmer assistance from related government agencies/agencies and empowerment of the role of Gapoktan. Farmers continue to optimize aid to the government to become independent and prosperous farmers the role of Gapoktan contributes to improving the quality of human resources, production, and agricultural productivity.